Polymer microextraction column for in-situ growth of MOF (Metal Organic Framework) and preparation and application thereof
By growing MOFs in situ in the polymer microextraction column, using self-assembly technology of metal oxide nanoparticles and organic linkers, the problem of easy shrinkage and lack of mesoporosis in the organic solvent is solved, achieving high efficiency The enrichment and stability of organic pollutants are improved, suitable for trace detection of environmental and biological samples.
Patent Information
- Application Number
- CN202411507270.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Existing polymer monolithic columns are prone to shrink or swell in the presence of organic solvents, and lack sufficient mesopores and interaction sites, resulting in low extraction efficiency of small molecules and short column life, and the application of MOF in separation analysis is limited.
Using a polymer microextraction column for growing MOFs in situ, self-assembly by introducing metal oxide nanoparticles and organic linkers into the solvent to form a polymer integral column matrix rich in metal oxides, and using ionic liquid porogenic agents The system achieves controllable growth of MOF and improves the specific surface area and stability of the column.
Achieve efficient hybridization of MOF and polymer, provides large specific surface area, multiple interaction sites and good thermal and chemical stability, significantly improves the ability to enrich persistent organic pollutants, and is suitable for the environment and biology. Trace detection of samples.
Smart Images

Figure CN119215480A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a polymer microextraction column with in-situ growth of MOF in a capillary porous continuous bed, a preparation method thereof, and application thereof in enrichment analysis of persistent organic pollutants. Background Art
[0002] A monolithic column is a continuous porous monolithic material formed by in-situ polymerization or immobilization in a column. It has an interconnected hierarchical porous network consisting of through-pores, mesopores and micropores. The surface of the material can be functionalized as needed. It is the preferred material for chromatography and catalysis applications. The polymer microextraction (PMME) technology based on capillary monolithic columns has the advantages of simple column preparation, low cost, high mass transfer rate, and low sample consumption. It is widely used in the separation and analysis of trace organic pollutants. However, since polymer monolithic columns usually lack sufficient mesopores and interaction sites, the specific surface area and mechanical strength are relatively low. In the presence of organic solvents, the column is prone to shrinkage or swelling, resulting in lower extraction efficiency for small molecules and shortened column life.
[0003] Introducing advanced porous materials with high stability, high specific surface area and adjustable porosity into organic polymer monoliths is one of the effective ways to increase the fixed specific surface area and the interaction sites with small molecules. Metal-organic frameworks (MOFs) are a type of inorganic-organic hybrid materials formed by self-assembly of metal ions (metal clusters) and organic ligands through coordination bonds. They have the characteristics of large porosity, easy modification, large specific surface area, and regular pore structure. They can be regarded as the basic unit for building various functional materials. The synthesis method of MOF is highly versatile, and thousands of MOF structures have been discovered. However, due to the powder morphology and small particle size of MOF itself, its application in separation analysis is limited. Studies have shown that MOF can affect the structure of polymers, while polymers can regulate the growth and properties of MOF. Therefore, hybridizing crystalline MOF with flexible polymer monoliths will effectively combine the advantages of both and provide an ideal extractant for PMME.
[0004] At present, there are three methods for preparing MOF-based hybrid polymer monoliths: (1) physical embedding method: pre-prepared MOF crystals are dispersed into the polymerization solution, and MOF hybrid monoliths are prepared by a one-pot method; (2) chemical bonding method: MOF is functionalized to have active sites on its surface that can undergo polymerization reactions, and the modified MOF participates in the polymerization reaction as a functional monomer; (3) continuous layer-by-layer assembly method (LbL): MOF precursor solution is alternately passed through the polymer monolith multiple times to form a MOF thin layer. However, due to the compatibility limitations between MOF and polymer, physical embedding and chemical bonding methods can only prepare low-content MOF hybrid monoliths, and the uniform distribution of MOF in the monolithic stationary phase is still difficult to effectively control. Its pore structure may be embedded in the polymer scaffold, resulting in separation or enrichment efficiency that is difficult to achieve the expected effect, and the advantages of MOF cannot be fully utilized. Although the cumbersome LbL method can better control the growth of MOF on the surface of porous monoliths and is suitable for forming MOF thin films, the assembly process is time-consuming and requires a large amount of organic solvents. Therefore, it is necessary to develop a new strategy for the rapid and efficient hybridization of MOFs with porous polymers. Summary of the invention
[0005] The purpose of the present invention is to provide a polymer microextraction column for in-situ growth of MOF and a preparation method thereof. The synthesized MOF hybrid polymer effectively and synergistically integrates the crystallinity and porosity of the metal organic framework and the flexibility and processability of the polymer, and has the characteristics of high specific surface area, stability and multiple interactions. Therefore, it can be used as a polymer microextraction column in conjunction with liquid chromatography, capillary liquid chromatography or LC-MS to achieve highly sensitive detection of trace persistent organic pollutants in environmental and biological samples.
[0006] To achieve the above object, the present invention adopts the following technical solution: One of the purposes of the present invention is to protect a polymer microextraction column for in-situ grown MOF, which is formed by in-situ self-assembly of a polymer monolithic column matrix hybridized with an organic linker and metal oxide nanoparticles in a solvent; wherein the metal oxide nanoparticle hybridized polymer monolithic column matrix is formed by thermally initiated free radical polymerization of multifunctional monomers and nano-metal oxides (MO-NPs) under the action of an initiator and an ionic liquid porogen system.
[0007] Furthermore, the organic linker is any one of 2-methylimidazole, trimesic acid, terephthalic acid, and 2,3-diaminoterephthalic acid (1,4-benzenedicarboxylic acid).
[0008] Furthermore, the solvent is one of water, N,N-dimethylformamide / water, ethanol / water or nitric acid / hydrogen fluoride / water.
[0009] Furthermore, the multifunctional monomer is composed of a fluorine-functionalized organic monomer containing a double bond and one or two organic monomers containing double bonds. Specifically, the fluorine-functionalized organic monomer containing a double bond may be, for example, dodecafluoroheptyl methacrylate, 2-(trifluoromethyl)acrylic acid, 3-(perfluoro-3-methylbytyl)-2-hydroxypropylacrylate; the organic monomer containing a double bond may be, for example, methacrylic acid, methyl acrylate, butyl methacrylate, 2-hydroxyethyl methacrylate, ethylene dimethacrylate, trimethylolpropane trimethacrylate, dodecylmethacrylate.
[0010] Furthermore, the nano metal oxide is any one of MOF phase metal oxides such as nano zinc oxide (ZnO), nano aluminum oxide (Al2O3), nano copper oxide (CuO), and nano iron oxide (Fe2O3).
[0011] Furthermore, the initiator is azobisisobutyronitrile (AIBN).
[0012] Furthermore, the ionic liquid porogen system is a mixture of 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazoliumtetrafluoroborate or 1-octyl-3-methylimidazolium tetrafluoroborate and n-propanol; the mass ratio of n-propanol in the mixture is 23-48%.
[0013] The second object of the present invention is to protect the preparation method of the polymer microextraction column of the in-situ growth MOF, which first introduces metal oxide nanoparticles to prepare a polymer monolithic column matrix rich in metal oxide nanoparticles on the surface, and then uses the in-situ self-assembly of metal oxides and organic linkers in the solution to anchor MOF crystals to the surface of the polymer monolithic material to obtain the polymer microextraction column of the in-situ growth MOF. It specifically includes the following steps: 1) Mix 3-9 mg of nano-metal oxide, 30-60 mg of multifunctional monomer and 1-3 mg of initiator, add 140-170 mg of ionic liquid porogen system, vortex at room temperature for 5 min, and ultrasonically degas for 10 min to form a uniform prepolymer solution; 2) injecting the prepolymer solution obtained in step 1) into a quartz capillary treated with γ-methacryloxypropyltrimethylsilane (γ-MAPS), sealing both ends with silicone rubber plugs, placing in a water bath at 85-95° C. for reaction for 5-15 min, and then rinsing with methanol to remove the ionic liquid porogen system and unreacted monomers, thereby obtaining a polymer monolithic column matrix rich in metal oxide nanoparticles on the surface; 3) Add 10-20 mL of solvent to 40-400 mg of organic linker and sonicate for 5-15 min at room temperature to completely dissolve it to form a uniform and transparent solution; 4) Pumping the organic linker solution obtained in step 3) into the polymer monolithic column obtained in step 2) for 0.5-2 h, and then sealing both ends of the column; 5) placing the monolithic column obtained in step 4) in a 60-70° C. water bath to react for 16-24 h, and then washing with methanol for 1 h to remove the unreacted solution, thereby obtaining the polymer microextraction column.
[0014] The third purpose of the present invention is to protect the application of the polymer microextraction column of the in-situ grown MOF in the enrichment analysis of persistent organic pollutants.
[0015] Furthermore, the persistent organic pollutants include persistent organic fluorine pollutants such as perfluorinated compounds and fluoroaromatic compounds.
[0016] The significant advantages and positive effects of the present invention are: (1) The present invention adds metal oxide nanoparticles to the prepolymer solution to prepare the monolithic column material, and realizes the controllable growth of the MOF coating in the tube by in-situ self-assembly. Metal oxides with different structures can be used as the metal source of MOF to grow the desired MOF. By simply adjusting the parameters that affect the dissolution of metal oxides and the crystallization of MOF, the in-situ growth of MOF can be regulated. At the same time, on the basis of the same metal oxide, MOF regulation can be further achieved by introducing different organic linkers. The preparation method is simple, economical and easy to operate, and has good universality.
[0017] (2) The present invention develops a new strategy for efficient and rapid hybridization of MOF and porous polymer monolithic materials. The prepared hybrid polymer microextraction column has the advantages of both MOF and flexible porous polymer materials, with large specific surface area, high mass transfer rate, suitable pores, and good thermal and chemical stability. At the same time, since the microextraction column is rich in F atoms and open metal sites, it can provide hydrogen bonding, FF affinity, and Lewis acid / base complexation, etc. It has an efficient enrichment effect on persistent organic fluorine pollutants such as perfluorinated compounds and fluoroaromatic compounds, and has broad application prospects in the pretreatment of environmental and biological samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Scanning electron microscope morphology images of ZnO NPs hybrid polymer monoliths prepared with different ZnO NPs dosages (ad is magnified by 1000, eh is magnified by 10000, and il is magnified by 30000).
[0019] Figure 2 These are the N2 adsorption-desorption isotherms of the ZIF-8 polymer microextraction columns prepared with different 2-methylimidazole dosages.
[0020] Figure 3 Scanning electron micrographs of the prepared ZnO NPs hybrid polymer monolithic column and the in situ grown ZIF-8 polymer microextraction column.
[0021] Figure 4 XRD diffraction patterns of the prepared ZnO NPs hybrid polymer monolithic column and the in situ grown ZIF-8 polymer microextraction column.
[0022] Figure 5 N2 adsorption-desorption isotherms of the prepared ZnO NPs hybrid polymer monolithic column and the in situ grown ZIF-8 polymer microextraction column.
[0023] Figure 6 TIC chromatograms of three perfluoroalkylphosphoric acids (PFPAs) analyzed using the ZnO NPs hybrid polymer monolithic column (a) and the in situ grown ZIF-8 polymer microextraction column (b).
[0024] Figure 7 TIC chromatograms of spiked serum samples containing three perfluoroalkyl phosphoric acids (PFPAs) analyzed using a polymer microextraction column grown on in situ ZIF-8, where a is perfluorohexylphosphonic acid (PFHP), b is perfluorooctylphosphonic acid (PFOP), and c is perfluorodecylphosphonic acid (PFDP). DETAILED DESCRIPTION
[0025] A polymer microextraction column for in-situ growth of MOF, the preparation of which comprises the following steps: 1) Mix 3-9 mg of nano-metal oxide, 30-60 mg of multifunctional monomer and 1-3 mg of initiator azobisisobutyronitrile, add 140-170 mg of ionic liquid porogen system, vortex at room temperature for 5 min, and ultrasonically degas for 10 min to form a uniform prepolymer solution; 2) injecting the prepolymer solution obtained in step 1) into a quartz capillary treated with γ-methacryloxypropyltrimethylsilane (γ-MAPS), sealing both ends with silicone rubber plugs, placing in a water bath at 85-95° C. for reaction for 5-15 min, and then rinsing with methanol to remove the ionic liquid porogen system and unreacted monomers, thereby obtaining a polymer monolithic column matrix rich in metal oxide nanoparticles on the surface; 3) Add 10-20 mL of solvent to 40-400 mg of organic linker and sonicate for 5-15 min at room temperature to completely dissolve it to form a uniform and transparent solution; 4) Pumping the organic linker solution obtained in step 3) into the polymer monolithic column obtained in step 2) for 0.5-2 h, and then sealing both ends of the column; 5) The monolithic column obtained in step 4) is placed in a 60-70°C water bath for reaction for 16-24 hours, and then rinsed with methanol for 1 hour to remove the unreacted solution, thereby obtaining a polymer microextraction column with MOF in situ growth.
[0026] Wherein, the nano metal oxide is any one of MOF phase metal oxides such as nano zinc oxide (ZnO), nano aluminum oxide (Al2O3), nano copper oxide (CuO), and nano iron oxide (Fe2O3).
[0027] The multifunctional monomer is composed of one of dodecafluoroheptyl methacrylate, trifluoromethylacrylic acid, and 3-(perfluoro-3-methylbutyl) 2-hydroxypropyl acrylate, and one or two of methacrylic acid, methyl acrylate, butyl methacrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, and lauryl methacrylate.
[0028] The ionic liquid porogen system is a mixture of 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate or 1-octyl-3-methylimidazolium tetrafluoroborate and n-propanol; the mass ratio of n-propanol in the mixture is 23-48%.
[0029] The organic linker is any one of 2-methylimidazole, trimesic acid, terephthalic acid, and 2,3-diaminoterephthalic acid.
[0030] The solvent is one of water, N,N-dimethylformamide / water, ethanol / water or nitric acid / hydrogen fluoride / water.
[0031] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0032] Example 1 (1) Alkenylation treatment of the inner wall of the capillary column The quartz capillary was rinsed with 0.1 mol / L hydrochloric acid solution for 1 h, then rinsed with deionized water for 30 min until neutral, then rinsed with 0.1 mol / L sodium hydroxide solution for 5 h, then rinsed with deionized water for 30 min until neutral, then rinsed with methanol for 30 min, and finally dried at 70 °C for 30 min in a 0.4 MPa, nitrogen environment; a mixed solution of 3-(methacryloyloxy)propyltrimethoxysilane and methanol in a volume ratio of 1:1 was injected into the quartz capillary treated above, and both ends were sealed with silicone rubber plugs. After reacting in a water bath at 60 °C for 24 h, it was taken out and rinsed with methanol for 30 min, and finally dried at 70 °C for 3 h in nitrogen to obtain an olefinated quartz capillary column.
[0033] (2) Preparation of ZnO NPs hybrid polymer monolithic column matrix Dodecafluoroheptyl methacrylate (DFA, 10 mg), methacrylic acid (MAA, 10 mg), ethylene glycol dimethacrylate (EDMA, 24 mg), ZnO NPs (0-9 mg), 1-hexyl-3-methylimidazolium tetrafluoroborate ([HMIM][BF4], 110 mg), n-propanol (46 mg), and initiator azobisisobutyronitrile (1 mg) were added to a centrifuge tube in sequence, and then vortexed at room temperature for 5 min and ultrasonically degassed for 10 min to form a uniform prepolymer solution; the prepolymer solution was injected into the olefin-modified quartz capillary obtained in step (1), sealed at both ends with silicone rubber stoppers, and placed in a 90 °C water bath for reaction for 15 min; after the reaction, the capillary monolith was taken out and rinsed with methanol to remove the porogen and unreacted monomers to obtain a ZnO NPs hybrid polymer monolith (ZnO@poly(EDMA-co-DFA-co-MAA)).
[0034] (3) Preparation of polymer microextraction column with in situ growth of ZIF-8 49.2-246 mg of 2-methylimidazole was weighed and dissolved in 10 mL of N,N-dimethylformamide / water solution (DMF / H2O=1:1, v / v) to obtain a 2-methylimidazole solution; the ZnO NPs hybrid polymer monolith prepared in step (2) was activated with methanol for half an hour; then the obtained 2-methylimidazole solution was passed through the ZnO NPs hybrid polymer monolith at a flow rate of 0.02 mL / min for 2 hours, and then both ends of the monolith were sealed with silicone rubber plugs and placed in a 70°C water bath for reaction for 20 hours; then the monolith was taken out and rinsed with methanol for 1 hour to remove the unreacted solution, thereby obtaining an in situ grown ZIF-8 polymer microextraction column (ZIF@poly(EDMA-co-DFA-co-MAA)).
[0035] Table 1
[0036] Since the ZnO-NPs fixed in the ZnO NPs hybrid polymer monolith can be used as metal sources and anchoring seeds for the in-situ growth of ZIF-8 crystals, the content of ZnO-NPs in the prepolymer solution not only affects the permeability of the ZnO NPs hybrid polymer monolith, but also has a significant impact on the subsequent growth of ZIF-8 crystals. As can be seen from Table 1, when the ZnO-NPs content is 0 mg, the prepolymer solution cannot form a column; and as the amount of ZnO-NPs in the prepolymer solution increases, the permeability K increases from 10.4×10 -14 m 2 Down to 3.3×10 -14 m 2 ZnO-NPs are embedded into the polymer monolith via electrostatic interaction. Figure 1 It can be seen that with the increase of the amount of ZnO-NPs in the prepolymer solution, the structure of the monolithic column becomes more compact, but when the ZnO-NPs content increases to 9 mg, the column body separates from the column wall (d). At the same time, more microspheres can be seen in the porous network structure of the ZnO NPs hybrid polymer monolithic column. This is because the ZnO-NPs in the prepolymer solution act as seeds for polymer nucleation, limiting the further growth of polymer microspheres, resulting in a denser porous structure of the ZnO NPs hybrid polymer monolithic column. Among them, the ZnO NPs hybrid polymer monolithic column prepared with 7 mg ZnO-NPs has a large number of large flow pores and uniform microsphere clusters, which can provide suitable permeability for PFPAs, and thus can show better extraction efficiency. Therefore, 7 mg ZnO-NPs is the optimal amount of nanometal oxide added to prepare ZnONPs hybrid polymer monolithic columns.
[0037] The chemical transformation of ZnO-NPs to ZIF-8 nanocrystals is based on the dissolution-precipitation equilibrium of ZnO-NPs and mainly involves two key steps: 2+ The release rate and Zn 2+ The coordination rate with 2-methylimidazole is related to the dosage of 2-methylimidazole. Therefore, the dosage of 2-methylimidazole is an important factor to be considered. Figure 2 The N2 adsorption-desorption isotherms of ZIF-8 polymer microextraction columns prepared with different 2-methylimidazole dosages. Figure 2 It can be seen that when the dosage of 2-methylimidazole increases from 49.2 mg to 147.6 mg, the N2 adsorption-desorption isotherm of the ZIF-8 polymer microextraction column changes from Type II to Type IV, that is, the nitrogen adsorption amount increases significantly when the relative pressure P / P0 is less than 0.1, and the specific surface area also increases from 40.37 m 2 g -1 Increased to 71.61 m 2 g -1 , indicating that the micropores in the hybrid monolithic column increased, and the successful transformation of ZnO-NPs to ZIF-8 nanocrystals was achieved; further increasing the amount of 2-methylimidazole, the specific surface area and average pore size of the ZIF-8 polymer microextraction column did not change significantly, indicating that the chemical transformation of ZnO-NPs to ZIF-8 nanocrystals was basically complete. Therefore, 147.6 mg of 2-methylimidazole is the optimal amount for constructing a polymer microextraction column for in situ growth of ZIF-8.
[0038] The ZnO NPs hybrid polymer monolithic column prepared under the selected optimal conditions and the polymer microextraction column with in situ grown ZIF-8 were further compared.
[0039] Figure 3The following are scanning electron microscope images of the prepared ZnO NPs hybrid polymer monolith and the polymer microextraction column with in situ growth of ZIF-8. As can be seen from the figure, both prepared column materials are well bonded to the inner wall of the capillary, without cracking and shrinkage. At the same time, compared with the ZnO NPs hybrid polymer monolith, the surface of the polymer microextraction column with in situ growth of ZIF-8 is composed of more small spheres, which is more compact as a whole, and the obtained particles are similar to the ZIF octahedral crystal form, indicating that ZIF crystals with complete crystal form have been successfully grown in situ in the ZnONPs hybrid polymer monolith.
[0040] Figure 4 The XRD diffraction patterns of the prepared ZnO NPs hybrid polymer monolith and the polymer microextraction column with in situ growth of ZIF-8. As can be seen from the figure, the ZnO NPs hybrid polymer monolith shows three weak diffraction peaks at 2θ of 30-40°, indicating the successful introduction of ZnO NPs. Compared with the ZnO NPs hybrid polymer monolith, the polymer microextraction column with in situ growth of ZIF-8 has new diffraction peaks in the low diffraction angle range and is consistent with the simulated spectrum of ZIF-8, confirming the transformation of ZnONPs into ZIF-8 crystals.
[0041] Figure 5 The N2 adsorption-desorption isotherms of the prepared ZnO NPs hybrid polymer monolith and the in situ grown ZIF-8 polymer microextraction column. As can be seen from the figure, the ZnO NPs hybrid polymer monolith is a typical Type II isotherm, mainly with large pores and a specific surface area of only 20.12 m 2 g -1 The adsorption capacity of the polymer microextraction column with in-situ ZIF-8 increased rapidly at a lower relative pressure, showing a typical Type IV isotherm. This can be attributed to the fact that the ZIF-8 crystal layer grown in-situ on the surface of the microextraction column provides microporous properties for the material, increasing the specific surface area of the hybrid material to 71.61 m 2 g -1 .
[0042] Example 2 In order to verify the enrichment performance of the prepared in situ grown ZIF-8 polymer microextraction column for persistent organic fluorine pollutants, three perfluoroalkylphosphoric acids (PFPAs) were extracted using the polymer microextraction column prepared under the optimal conditions in Example 1, and the trace PFPAs in complex biological samples were detected in combination with LC-MS coupling technology. The specific extraction and detection conditions are as follows: (1) Extraction: A capillary microextraction column (250 μm id×375 μm od×5 cm) was activated with methanol and loading solvent (methanol solution at pH 7) for half an hour, respectively. Then, 1 mL of sample was introduced at a flow rate of 60 μL / min, and then the unbound sample on the surface was washed away with loading solvent. Then, 50 μL of 3.5% formic acid / acetonitrile (1 / 9 v / v) was used for elution, and the elution tail was collected.
[0043] (2) LC-MS detection: The chromatographic conditions were a C18 column (150×2.1 mm id, 5 μm), mobile phase A was 0.1% ammonia solution, mobile phase B was methanol, gradient elution mode was used, and the total flow rate was 0.3 mL / min; the gradient elution program was: 0.0-2.5 min=30-70% (v / v) B, 2.5-4 min=70% B, 4-6 min=70%-30% B, 6-8min=30% B. The injection volume was 10 μL. The mass spectrometry conditions were MS tuning in multiple reaction monitoring (MRM) mode using negative ion electrospray ionization (ESI). The MS parameters of the three PFPAs were: parent ion m / z PFHP =399.1, m / z PFOP =499.0, m / z PFDP =598.9; the product ions of the three are all m / z=79.0; the collision energies are PFHP: 44 eV, PFOP: 40 eV, PFDP: 42 eV.
[0044] Figure 6 In order to analyze perfluorohexylphosphonic acid (PFHP, 5 μg L) using ZnO NPs hybrid polymer monolithic column and in situ grown ZIF-8 polymer microextraction column, respectively. -1 ), perfluorooctylphosphonic acid (PFOP, 0.5 μg L -1 ) and perfluorodecylphosphonic acid (PFDP, 5 μg L -1 ), where a and b are the ZnO NPs hybrid polymer monolith and the in-situ grown ZIF-8 polymer microextraction column, respectively. As can be seen from the figure, compared with the ZnO hybrid polymer monolith, the in-situ grown ZIF-8 polymer microextraction column exhibits better extraction performance for the three targets, indicating that the ZIF-8 crystal layer in-situ grown on the polymer matrix provides the extraction column with a high specific surface area and abundant action sites.
[0045] Figure 7 In order to analyze blank serum samples and serum samples containing PFHP (5 μg L) using the polymer microextraction column grown in situ on ZIF-8, -1 ), PFOP (0.5 μg L -1), PFDP (5 μg L -1 ) of the spiked serum samples, where a is PFHP, b is PFOP, and c is PFDP. As can be seen from the figure, the spiked recoveries of the three target substances in serum samples at three spiked concentrations were 70.0-91.2%, respectively, with RSDs of 3.4-6.5%, indicating that the enrichment using the prepared in situ grown ZIF-8 polymer microextraction column has good accuracy and reproducibility.
[0046] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A polymer microextraction column for in-situ growth of MOF, characterized in that: The polymer microextraction column is formed by in-situ self-assembly of a polymer monolithic column matrix hybridized with an organic linker and metal oxide nanoparticles in a solvent; wherein the polymer monolithic column matrix hybridized with metal oxide nanoparticles is formed by thermally initiated free radical polymerization of multifunctional monomers and nano-metal oxides under the action of an initiator and an ionic liquid porogen system.
2. The polymer microextraction column for in-situ growth of MOF according to claim 1, characterized in that: The organic linker is any one of 2-methylimidazole, trimesic acid, terephthalic acid, and 2,3-diaminoterephthalic acid.
3. The polymer microextraction column for in-situ growth of MOF according to claim 1, characterized in that: The solvent is one of water, N,N-dimethylformamide / water, ethanol / water or nitric acid / hydrogen fluoride / water.
4. The polymer microextraction column for in-situ growth of MOF according to claim 1, characterized in that: The multifunctional monomer is composed of a fluorine-functional organic monomer containing a double bond and one or two organic monomers containing double bonds.
5. The polymer microextraction column for in-situ growth of MOF according to claim 1, characterized in that: The nano metal oxide is any one of nano zinc oxide, nano aluminum oxide, nano copper oxide and nano iron oxide.
6. The polymer microextraction column for in-situ growth of MOF according to claim 1, characterized in that: The initiator is azobisisobutyronitrile.
7. The polymer microextraction column for in-situ growth of MOF according to claim 1, characterized in that: The ionic liquid porogen system is a mixture of 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate or 1-octyl-3-methylimidazolium tetrafluoroborate and n-propanol; the mass ratio of n-propanol in the mixture is 23-48%.
8. A method for preparing a polymer microextraction column for in-situ growth of MOF according to any one of claims 1 to 7, characterized in that: The specific steps include: 1) Mix 3-9 mg of nano-metal oxide, 30-60 mg of multifunctional monomer and 1-3 mg of initiator, add 140-170 mg of ionic liquid porogen system, vortex at room temperature for 5 min, and ultrasonically degas for 10 min to form a uniform prepolymer solution; 2) injecting the prepolymer solution obtained in step 1) into a quartz capillary, sealing both ends with silicone rubber plugs, placing in a water bath at 85-95° C. for reaction for 5-15 min, and then washing with methanol to remove the ionic liquid porogen system and unreacted monomers to obtain a metal oxide nanoparticle hybrid polymer monolithic column matrix; 3) Add 10-20 mL of solvent to 40-400 mg of organic linker and sonicate for 5-15 min at room temperature to completely dissolve it to form a uniform and transparent solution; 4) Pumping the organic linker solution obtained in step 3) into the polymer monolithic column obtained in step 2) for 0.5-2 hours and then sealing both ends of the column; 5) placing the monolithic column obtained in step 4) in a 60-70° C. water bath to react for 16-24 h, and then washing with methanol for 1 h to remove the unreacted solution, thereby obtaining the polymer microextraction column.
9. Use of a polymer microextraction column with in-situ growth MOF as claimed in any one of claims 1 to 7 in enrichment analysis of persistent organic pollutants.
10. The use according to claim 9, characterized in that: The persistent organic pollutants include perfluorinated compounds and fluoroaromatic compounds.
Citation Information
Patent Citations
Method for preparing liquid chromatography monolithic column based on metal-organic frameworks
CN102631796A
Metal ion immobilization modified silica monolithic column and preparation method thereof
CN106823466A
Preparation method of organic-inorganic hybrid monolithic column
CN110090634A
Preparation of quartz capillary hybrid monolithic column based on metal-organic frameworks (MOFs)
CN111359587A
Group iv metal oxide monolithic columns
US20100140154A1
Cited By
Integrated water treatment process coupling pollutant mineralization and adsorbent preparation
CN120191987A
An integrated water treatment process coupling contaminant mineralization and sorbent production
CN120191987B